The percentage method Rotch on artificial feeding - Eyzaguirre, Rómulo (1920)
There surely means promoting formula feeding, the earnestness that pediatricians everywhere, have to find the best ways of not only resemble cow's milk to human milk, but modifying the first so that it could serve the best success, clinical needs. This and childcare, have always required a good preparation to flee as possible empirical procedures and approaches to scientific truth. But as the situation of the pediatrician is to vary greatly, and Advancement as necessary in each case there scientific procedures for modifying cow's milk, which does not allow but one guy in the amendment, which by its nature unchanged by their permanent status, can only be used in certain cases, and will be used only moderately in many others. Modified milks GAERTNER of BACKAUS of VIGIER, Dufour, MONTI, etc., used between us, be very scientific basis, not satisfied at all times, because their preparation obeys rules that make up a single correction mode, and despite this, however they preferably have the American method. which has the advantage of varying the type of modification as much as you want, or need be taken.